Islamic economic thoughts according to Ibn Khaldun, Al-Maqrizi, and Al-Syatibi - Saputra, Tri Agung (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2021)
Purpose – This article explores Islamic economic thought according to Ibn Khaldun, Al-Maqrizi, and Al-Syatibi. One of Ibn Khaldun's thoughts that is very prominent and very important to discuss is economics.Method – The research used qualitative methods by analyzing the direction of thought and the construction of the Islamic economic system from Ibn Khaldun, Al-Maqrizi, and AL-Syatibi using the maqashid sharia concept.Result – The importance of discussing Ibn Khaldun's thoughts on economics is because his thoughts have great significance for developing Islamic economics in the future.Implication – The concept of maqashid sharia put forward by Asy-Syatibi should be a reference in every analysis process related to economic behavior. The system and science currently being formulated can be a solution to the increasingly acute economic complex.Originality – This study compares the Islamic economic thoughts of three prominent figures, i.e., Ibn Khaldun, Al-Maqrizi, and Al-Syatibi.